PENERAPAN LAYANAN INFORMASI TEKNIK MIND MAPPING UNTUK MENINGKATKAN PEMAHAMAN BAHAYA PERILAKU MEROKOK - Fata Rafi'u Hakam; Kusnarto Kurniawan (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2019)
This study aims (1) to find out the description of the dangers of smoking behavior of students before and after the application of mind mapping technique information services, (2) to determine the effect of mind mapping technique information services on increasing the understanding of the dangers of smoking behavior of students. The research method uses experiments with pre-experimental design and type of the one group pre-test and post-test. Data collection techniques used psychological scale with a scale of 38 items of the understanding of the dangers of smoking behavior. The population of students of class XI Multimedia 1 SMK 4 Semarang with a sample of 36 people who were determined purposively. Data analysis techniques used (1) descriptive statistical analysis to describe the understanding of the dangers of smoking behavior of students before and after treatment, (2) hypothesis testing with t-test analysis to determine the effect of applying mind mapping techniques before and after treatment. The results showed that information services with mind mapping techniques influence the increase in understanding of the dangers of smoking behavior of students. Understanding the dangers of student smoking behavior increases after being given information service treatment with mind mapping techniques. So mind mapping technique information services can be used as an alternative to increase understanding of the dangers of smoking behavior in students.